An Analysis of Princess Merida’s Masculinity and Femininity Character in The Movie fo “Brave” - Nugraheni, Susari; Ardyani, Aulia Nanda; Fasikh, Mukhlasul; Resmisari, Diah (STIBA IEC JAKARTA, 2025)
The former Disney Princess movies mostly represent women as the ones who are helpless and require men to save them. The objectives of this study are to find out the masculinity and femininity characters and the reasons on why the main character has masculinity and femininity. In this research, the writers used the method of qualitative research leads to theory Feminism by Mary Wollstonecraft. The data were collected through the scenes and dialogue in the movie. The data were collected through the scenes and dialogues in the movie. The data were analyzed by sorting, classifying, interpreting and describe a conclusion which is suitable with the concept of Masculinity and Femininity character. From this research, it is found that the main character of the movie has two traits in her behavior. It is happened because of her environment and her parents. The result of analysis showed that the main character has six traits, consist of: Adventurous, Willing to Take a Risk, Independent, Brave, Affection and Elegant. The writers found in the movie analysis experienced by the main character include: Masculinity and Femininity. The writers hoped the readers could learn and understand knowledge about the character of masculinity and femininity in literary works related to their characteristics and struggles in the story of a literary work.